PENGEMBANGAN KOTA BOGOR SEBAGAI DESTINASI PARIWISATA INTERNASIONAL - Mulyana, Bedi (Jurnal Ilmiah Pariwisata; Volume 2 No.1 Hal 109-222 September 2012, 2012)
The research aims to identify factors that became a tourist attraction in the city of Bogor, Indonesia (supply side) and discussed the international tourists who visited this city (demand side). In addition to the enhancements described with the support of the local government that serves as a facilitator for the development of tourism in terms of the Bogor City’s policies and planning. A regional area of the city’s tourist development is very important to promote development and improve the interconnected regional economy, including the development of the city as international tourist destination. The study was conducted by survey techniques (questionnaire surveys, interviews and observation and study of literature to support the research) using the approach of demand and supply in the Bogor City tourism development as an international tourist destination. The study's findings can be considered for Bogor City tourism development as an international destination. Furthermore, the government together with other tourism stakeholders must coordinate and cooperate in realizing the Bogor City tourism development that better in the future.
Keywords: Bogor City tourism, supply and demand, development destination